Model Green Economy Index dalam Mengukur Transformasi Pembangunan Berkelanjutan di Indonesia - Rizka Fadillah; Andria Zulfa; Rusiadi Rusiadi; Bakhtiar Efendi; Lia Nazliana Nasution (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The Green Economy Index is an economic concept that prioritizes a sustainable economy and has a correlation to sustainable development. Green Economy not only includes aspects of economic growth but also places the importance of environmental sustainability, social empowerment as the first foundation. This aspect is the purpose of the research to form a strong basis in building an economic model that not only provides short, medium and long term benefits for society and the environment but can continue sustainable development in Indonesia. VAR (Vector Auto Regression) in the context of econometric analysis is a statistical method used to model the relationship between several variables using time series data. The analysis shows that the estimation results highlight that the contribution of Green Economy Index variables in measuring sustainable development transformation on economic growth variables is mainly influenced by energy consumption and carbon emissions, showing a significant impact of energy consumption and carbon emissions. Green investment in the short and medium term has the greatest influence by green investment itself, but in the long term the effect on green investment is carbon emissions and energy consumption. Furthermore, the variables of energy consumption and carbon emissions that have a significant effect are the variables themselves. IRF analysis shows the response of variables to changes and the importance of response stability in the short, medium and long term. In the Green Economy Index Model, energy consumption and carbon emissions become the main pillars with the encouragement of increasing green investment and then increasing economic growth. The analysis confirms the importance of adopting environmentally friendly practices, using renewable energy and increasing green investment in promoting sustainable economic growth without compromising the environment.